Six New Triterpenoidal Glycosides Including Two New Sapogenols from Albizziac Cortex. V - IKEDA, Tuyoshi; TAKEMOTO, Norimichi; HIGUCHI, Hiroyuki; IDA, Yoshiteru; FUKUI, Katsura; ARAKI, Kaoru; SHOJI, Junzo; NOHARA, Toshihiro; KINJO, Junei; MIYAKOSHI, Masazumi (Chem. Pharm. Bull, 1992)
Six new triterpenoid glycosides called julibrosides A1-A4, B1 and C1 were isolated from Albizziae Cortex, the dried stem bark of Albizzia julibrissin DURAZZ. Their structures were determined based on spectral and chemical evidence. Julibrosides B1 and C1 had new sapogenols, designated julibrogenin B and C, respectively, while julibrosides A3 included N-acetyl-D-glucosamine as a sugar component.